A Survey on Outsourced Attribute-Based Encryption Technique - Rafiq Mir, Hadiya; Jogalekar, UA (International Journal of Computer Sciences and Engineering, 2025)
In the modern times, more sensitive data is being stored on third party servers which are untrusted, so data on these sites need to be in encrypted form. Every now and then new encryption techniques are put forward. Attribute Based Encryption (ABE) is one such cryptographic technique that secures the data and provides fine-grained access control. However, The Computational complexities of ABE key issuing and decryption are getting too high due to the high expressiveness of ABE approach which affects the efficiency of ABE. To tackle this, many Outsourced Variants of ABE have been proposed to improve the efficiency of ABE such that it could be widely deployed. In this paper, a survey is done on various ABE techniques that have been proposed and their advantages and disadvantages are also discussed.